Comparison and agreement between arterial versus venous blood gas analysis and pulse oxymetry in children with acute asthma - Nair, Sreenath G.; Cherian, Carol Sara; Sushmabai, S. (International Journal of Research in Medical Sciences, 2022)
Background: Blood gas analysis is critical in managing children in intensive care unit primarily in respiratory disorders. This study aimed to ascertain agreement between the arterial and peripheral venous measurement of pH, pCO2, pO2 and bicarbonate levels along with SpO2 in acute asthma. Methods: Hospital based cross sectional analytical study was conducted at Pushpagiri Institute of Medical Sciences in 50 children within the age group of 5-15 years who presented with symptoms suggestive of acute asthma with a modified PSI>6 after informed consent from parents and assent from child. SpO2 monitoring and ABG simultaneously with VBG were done immediately after admission. Statistical analysis was done to find out any correlation using Pearson correlation coefficient and Bland Altman plots were drawn to assess agreement. Results: 50 children in the age group 5 years to 15 years were included in the study. Arterial pH and venous pH were found to be correlated significantly, Pearson correlation coefficient r=0.438. There was a good correlation between the arterial and venous pCO2 with r= 0.610, bicarbonate values r=0.608. There was poor correlation between arterial PO2 and venous PO2 values (r=0.030). The bias plot for pH and pCO2 showed moderate agreement in with 95% limits of agreement being in acceptably narrow range. The mean bias in pH was 0.0242 (SD=0.04912, 95% limits of agreement = -0.0721 to 0.12045); bias in pCO2 was -4.04400 (SD=5.53616, 95% limits of agreement = -14.8949 to 6.8069), and in bicarbonate levels -0.0940 (SD=2.09, 95% limits of agreement = -4.1998 to 4.0119). Conclusions: Even though there was a good correlation and a moderate agreement between ABG and VBG parameters like pH, pCO2 and bicarbonate, VBG cannot be replaced for ABG in acute asthma. Pulse oximetry also has limitations in children with acute severe asthma as compared to ABG value.